(untitled) (Journal of Plant Disease Sciences, 2025)
Detection of seed-borne mycoflora of wheat (Triticum aestivum L.) was carried out during 2024–25 at the Department of Plant Pathology, Dr. Panjabrao Deshmukh Krishi Vidyapeeth (PDKV), Akola. The study aimed to identify the seed-borne mycoflora associated with different cultivars of wheat. Four incubation techniques, namely the standard blotter method, agar plate method, 2,4-D blotter method, and rolled paper towel method, were evaluated for their efficiency in detecting seed-borne fungi. A total of eight seed-borne fungal species were identified, namely Cladosporium cladosporioides, Alternaria alternata, Fusarium moniliforme, Curvularia lunata, Bipolaris sorokiniana, Aspergillus niger, Aspergillus flavus, and Rhizopus spp. Among the incubation methods, the agar plate method recorded the highest frequency of seed-borne mycoflora (93.25%), followed by the standard blotter method (87.00%), whereas the 2,4-D blotter method recorded 59.00%. The rolled paper towel method recorded the lowest detection of seed-borne mycoflora (35.75%). The standard blotter method proved most effective in detecting Cladosporium cladosporioides (23.00%) and Alternaria alternata (20.50%), while the agar plate method efficiently detected Curvularia lunata (13.75%) and Bipolaris sorokiniana (8.50%). Lower frequencies were observed for Aspergillus spp. and Rhizopus spp. across all incubation methods. It was concluded that the agar plate method and standard blotter method were more efficient for routine detection of seed-borne fungi in wheat. These methods are therefore recommended for seed health testing to ensure phytosanitary quality and disease-free seed production in wheat.